Developing Value : The Business Case for Sustainability in Emerging Markets - Cowe, Roger (London: SustainAbility Ltd., 2015)
Based on more than 240 real-life examples in over 60 countries, Developing Value is the first large-scale study analyzing the business case for sustainability in emerging markets, the opportunity for businesses to achieve benefits such as higher sales, reduced costs and lower risks from better corporate governance, improved environmental practices, and investments in social and economic development. It pinpoints the many opportunities available to diverse businesses in Africa, Asia, Central and Eastern Europe, the Middle East and Latin America. The report aims to help business people in emerging markets, identify opportunities to increase profits, by making progress on sustainability. It provides tools to assess, and conduct each business case, analyzing relevancy to emerging markets, i.e., opportunities for businesses to achieve high sales, reduced costs, and lower risks, from improved governance, environmental practices, and investments in socioeconomic development. The companies examined are ordinary businesses taking practical steps to address issues, and, evidence shows there are compelling reasons for action. Other specific opportunities to pursue sustainability include building regulations, developing human capital, and improving access to capital. All these opportunities are documented through case studies from Brazil, China, the Czech Republic, and South Africa. The study further examines variations in businesses by region, and company size, i.e., for small and medium sized enterprises, national companies, and multinational corporations, as well as foreign multinationals headquartered in developed countries, in addition to export-oriented companies, and those focused on domestic markets. Significantly, the study presents a business success case matrix, related to key aspects of sustainability, and recognized business factors, discussing practical steps towards implementation of strategies, priorities, and monitoring. The report is a joint effort by the International Finance Corporation of the World Bank, SustainAbility (United Kingdom), and Ethos Institute - Business and Social Responsibility (Brazil)